The virtues of happiness a theory of the good life - Bloomfield, Paul 1962- (Oxford moral theory, 2014)
Undeniably, life is unfair. So, why play fairly in an unfair world? The answer comes from combining the ancient Greek conception of happiness with a modern conception of self-respect. The book is about why it is bad to be bad and good to be good, and what happens in between